2018
DOI: 10.1038/s41598-018-19377-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Response of Caenorhabditis elegans to Simulated Microgravity by p38 Mitogen-Activated Protein Kinase Signaling

Abstract: The in vivo function of p38 mitogen-activated protein kinase (MAPK) signaling in regulating the response to simulated microgravity is still largely unclear. Using Caenorhabditis elegans as an assay system, we investigated the in vivo function of p38 MAPK signaling in regulating the response of animals to simulated microgravity and the underlying molecular mechanism. Simulated microgravity treatment significantly increased the transcriptional expressions of genes (pmk-1, sek-1, and nsy-1) encoding core p38 MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Li et al . 42 showed that simulated microgravity could significantly increase the expression of p38 MAPK signaling in the intestine, which may mediate a protection mechanism for animals against the adverse effects from simulated microgravity. Studies in space may provide information about human life that cannot be learned on Earth, including lessons about aging.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . 42 showed that simulated microgravity could significantly increase the expression of p38 MAPK signaling in the intestine, which may mediate a protection mechanism for animals against the adverse effects from simulated microgravity. Studies in space may provide information about human life that cannot be learned on Earth, including lessons about aging.…”
Section: Discussionmentioning
confidence: 99%
“…That is, during the control of toxicity of simulated microgravity, we also raised an intestinal signaling cascade of SKN-1a-GST-4/GST-5/GST-7. Our previous study has suggested that the activation of PMK-1/p38 MAPK-SKN-1 mediated a protective response to simulated microgravity 20 . In this study, we further found that the decrease in let-7 could further enhance the p38 MAPK signaling pathway-mediated protective response to simulated microgravity by targeting SKN-1 s. Our results in this study provided an important molecular basis for our understanding the epigenetic control of response to simulated microgravity in organisms.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, the toxicity of simulated microgravity could also be detected in nematodes 17 19 . Simulated microgravity could induce production of intestinal reactive oxygen species (ROS) and inhibition in locomotion behavior in nematodes 20 . Meanwhile, insulin, p38 mitogen-activated protein kinase (MAPK), and Wnt signaling pathways were required for toxicity induction in simulated microgravity treated nematodes 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…elegans Experiment in Space” (ICE-First) experiments as an example, it has been observed that microgravity could potentially at least cause the toxicity on early embryogenesis, muscle development, germline development, locomotion behavior, and reproduction in nematodes 1723 . The toxicity of simulated microgravity on nematodes could be further assessed more recently 2427 . The observed toxicity induced by simulated microgravity was under the control of insulin and p38 mitogen-activated protein kinase (MAPK) signaling pathways in nematodes 24,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of simulated microgravity on nematodes could be further assessed more recently 2427 . The observed toxicity induced by simulated microgravity was under the control of insulin and p38 mitogen-activated protein kinase (MAPK) signaling pathways in nematodes 24,26 .…”
Section: Introductionmentioning
confidence: 99%